(untitled) (Global Journal of Science Frontier Research, 2019)
The present study was conducted during 56 days to evaluate the effect of substituting fish meal (FM) with pre-treated Lima bean meal (LBM) on growth, feed utilization, and nutrient retention in Clarias gariepinus fingerlings weighing 3.00±0.02g. Four isonitrogenous (40% crude protein) diets containing 0% (D0), 25% (D25), 50% (D50) and 100% (D100) of LBM, as FM substitute were used. D0 was considered a control diet. The results obtained indicate no significant difference in weight gain (11.97±0.67g and 12.95±2.12g), specific growth rate (3.46±0.23%/day and 2.95±0.22%/day), protein efficiency ratio (0.89±0.01 and 1.05±0.02), protein retention (10.83±0.23% and 12.48±0.19%) and lipid retention (9.11±0.55% and 9.45±0.43%) of fish fed D0 and D100 respectively. Fish fed D25 and D50, showed significant growth increase, feed utilization performances, and both protein and lipid retention in comparison with D0 and D100. This study indicates that Lima bean meal can be used up to 50% in formulating feed for Clarias gariepinus fingerlings in rural areas.